THE IMPACT OF PREECLAMPSIA ON NEONATAL OUTCOMES AMONG LABORING MOTHERS: A STUDY AT THE GAYATRI WARD, DR. WAHIDIN SUDIRO HUSODO REGIONAL GENERAL HOSPITAL, MOJOKERTO - Indah Kusmindarti; Lusi Rusdiana (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Preeclampsia is one of the major pregnancy complications contributing to maternal and neonatal morbidity and mortality. Impaired uteroplacental perfusion in preeclampsia may lead to adverse neonatal outcomes, including asphyxia, prematurity, low birth weight (LBW), and intrauterine growth restriction (IUGR). To analyze the impact of preeclampsia in laboring mothers on neonatal outcomes. The research method used was descriptive research with an observational approach to examine the characteristics of patients with hypertension in labour at Dr. Wahidin Sudiro Husodo Regional General Hospital, Mojokerto City, in 2025-2026 This study employed a retrospective descriptive-analytic design. A total of 53 mothers with preeclampsia who met the inclusion criteria were included in the study. Data were collected from medical records and analyzed using univariate analysis to describe respondents' characteristics and Chi-square tests to determine the relationship between maternal age, parity, gestational age, and neonatal outcomes. Most mothers were aged 20–35 years (83.1%), multiparous (51%), delivered at term (85%), and underwent cesarean section (77.4%). Normal neonatal outcomes were found in 26 infants (49.1%), followed by asphyxia in 21 infants (39.6%), prematurity in 8 infants (15.1%), low birth weight in 4 infants (7.5%), and IUGR in 1 infant (1.9%). Maternal age and gestational age were associated with neonatal outcomes, whereas parity showed no significant association. Preterm infants had a higher risk of adverse neonatal outcomes compared to term infants. Preeclampsia in laboring mothers adversely affects neonatal outcomes, particularly increasing the risk of asphyxia, prematurity, low birth weight, and IUGR. Gestational age was identified as the most influential factor. Early detection and appropriate management of preeclampsia are essential to reduce neonatal complications